Double Antibiotic Paste for Management of External Inflammatory Root Resorption - Sabbagh, Sedigheh; Sarraf Shirazi, Alireza; Torabzadeh, Hassan (Iranian Endodontic Journal, 2018)
External inflammatory root resorption (EIRR) is one of the common complications following dental trauma which when remained untreated, may lead to tooth loss. Successful treatment outcomes depend on elimination of bacteria from root canal system and apical sealing. This case presents the endodontic management of an EIRR that was nonresponsive to calcium hydroxide (CH) therapy. An 11-year-old boy was referred for management of a traumatized maxillary central incisor. Tooth #8 was symptom-free, nonresponsive to vitality pulp tests and had an immature root with sever EIRR. Using chemomechanical debridement and CH dressing, the treatment was initiated. The tooth was remained asymptomatic; however, after five weeks the size of periradicular lesion increased and intracanal exudate was present, signifying a resistant endodontic infection. In second appointment, double antibiotic paste (DAP; ciprofloxacin/metronidazole) was applied to the canal. Eight weeks later, the tooth continued to be asymptomatic and the size of the lesion decreased. Finally, the root canal was entirely obturated with calcium-enriched mixture (CEM). At 18-month follow-up, the tooth was asymptomatic/functional, EIRR did not further progress and tooth discoloration was not observed. Based on the results, DAP has the potential to be used to manage the CH-resistant endodontic infection. Furthermore, CEM root filling/sealing seems to be an applicable choice in EIRR management. Keywords: Antibiotics; Calcium-Enriched Mixture; CEM Cement; Dental Trauma; Endodontics; Intracanal Medicament; Root Resorption